Finite element analysis of rotator cuff tendons - Chiew, Kevin Han Rong (Nanyang Technological University, 2021)
Rotator cuff tear is one of the common diseases of the shoulder, with the supraspinatus tendon being involved in most of the tears. Therefore, this study aims to analyse the stress distribution in the supraspinatus tendon using a validated three-dimensional (3D) finite element (FE) model of the rotator cuff tendons. Abaqus 2020 is used as the primary FE analysis software in this study. The strain, anatomical data and material properties collected from a cadaveric study [1] were used to validate the FE model. The strain of the FE model correlated significantly with the experimental strain (r = 0.89, r-p < 0.05). High maximum principal stresses were found on the articular surface of the supraspinatus tendon at the insertion, with the stress peaking at the anterior edge. Therefore, this may contribute to the initiation of tears on the articular surface of the tendon, which may explain the frequent occurrence of tears on this side. Additionally, high shear stresses were observed near the insertion of the supraspinatus tendon at elevated angles. Thus, this may initiate and propagate intratendinous tears, ultimately leading to the delamination of the tendon. A partial-thickness tear was created on the articular surface of the supraspinatus tendon in the FE model. High shear stresses were observed near the tip of the tear, and high maximum principal stresses were found at the anterior edge of the tear. Moreover, the presence of the tear led to an increase in shear stress and maximum principal stress across the tendon thickness at all angle of abduction tested except 15°. Thus, these biomechanical conditions may contribute to the propagation of the tear, resulting in a full-thickness tear. It is hoped that the results from this study can aid orthopaedic surgeons and physiotherapists in optimising the rehabilitation and treatment of rotator cuff tears